Dinámica del almacenamiento de carbono en una parcela permanente de bosque andino en el Parque Universitario “Francisco Vivar Castro”, Loja, Ecuador - Valdiviezo Ramirez, Jenniffer Natividad (2024)
Forests are one of the most valuable natural resources for humanity, because they provide ecosystem goods and services, including carbon storage, which contributes to reducing the effects of climate change. The aim of the study was to quantify biomass and carbon, and to analyse the relationship between carbon storage and the growth and mortality of Andean forest species in the "Francisco Vivar Castro" University Park (PUFVC). A permanent plot of 100 m × 100 m was demarcated in the study area, subdivided into 25 subplots of 400 m2 (20 × 20 m). Within each subplot, trees ≥ 5 cm DBH were measured in a first inventory conducted by Reyes (2017) and the second inventory conducted by Merchan Granda (2022). An allometric equation including DBH and species density was applied to quantify biomass and carbon. In addition, histograms were used to verify in which diameter class the greatest amount of biomass and carbon accumulated. Non-parametric analyses were used with the Kruskal-Wallis test and the correlation of biomass, growth and mortality was verified by applying Spearman's correlation. Temporal changes in forest structure were calculated with annual increment rate, annual increment rate in basal area, mortality and recruitment rate and forest half-life. In total, 1 370 individuals were recorded for 2017 and 1 214 individuals in 2022 in the Andean forest of the PUFVC, corresponding to 45 species, 38 genera and 29 botanical families. In the Andean forest, 105.68 Mg ha-1 and 49.66 Mg ha-1 of biomass and carbon were quantified, respectively, with a mortality rate of 4.68% and a recruitment rate of 1.81%. Carbon accumulation was highest in the second diameter class (10-20 cm DBH) with 15.45 Mg ha-1 . Trees stored an average of 4.03 Mg biomass per individual and had an abundance of 51 individuals per subplot. Alnus acuminata was the species that stored the most carbon with 14.26 Mg ha-1 . The species with the highest mortality were Palicourea amethystina, Phenax laevigatus, and Oreopanax rosei, while Phenax laevigatus, Palicourea amethystina and Palicourea heterochroma were those with the highest number of recruits. On the other hand, Axinaea macrophylla, Guettarda hirsuta, Alnus acuminata, Vismia baccifera and Oreopanax rosei were the species that showed an increase in carbon storage in five years. There was a positive and significant correlation (p=0.002) of 59% between carbon storage and tree recruitment. Carbon storage presented a significant negative correlation (p=0.03) of -45% with respect to growth; likewise, carbon storage presented a significant negative correlation (p=0.04) of -40% with the mortality rate. Carbon storage in the Andean forest and its relationship with forest dynamics (growth, mortality and recruitment) is fundamental to contribute to the mitigation of climate change and the conservation of these ecosystems.